Caesarean section and body mass index among danish men. (16th April 2013) - Svensson, Elisabeth; Hyde, Matthew; Modi, Neena; Ehrenstein, Vera
Abstract Objective: We conducted a prevalence study to examine the association between Caesarean section and body mass index (BMI) in 21, 051 adult Danish men born in 1977‐1983 who presented for mandatory conscription evaluation around age 18 years. Design and methods: Data on BMI from conscription records were linked to the men's birth records to identify mode of delivery and other perinatal data. Results: Two thousand one hundred thirty‐eight men (10%) had been delivered by a Caesarean section. Prevalence of obesity at conscription was 6% for those born vaginally and 9% for those born by a Caesarean section. The adjusted prevalence ratio (PR) for obesity (BMI ≥ 30 kg/m2) was 1.35 (95% CI 1.14‐1.60); the adjusted PR for overweight (25 ≤ BMI < 30 kg/m2) was 1.05 (95% CI 0.94‐1.17). The adjusted mean difference in BMI was 0.38 kg/m2 (95% CI 0.16‐0.60) comparing men born by Caesarean versus vaginal delivery. The estimates were similar for planned and nonplanned Caesarean deliveries. Conclusion: Birth by a Caesarean section was associated with an increased risk of obesity among men.